New International Order - Analysis of Trends and Alternatives of Future Visions in International Conflicts - Wizimirska, Klaudia (Journal of Applied Cultural Studies, 2016)
Currently, when the world is no longer divided into two political-military blocks, local conflicts have ceased to be a surrogate training ground of rivalry between two superpowers. In most cases, they do not therefore constitute a direct threat to the world peace. Although, after the collapse of the Eastern bloc, local conflicts have lost their strategic dimension, we still have to deal with increasing number of new trends among the conflicts in the world. They cause political instability in various regions and bring substantial suffering to the people, and death, famine and epidemics. Their development brings new challenges, and thus the new visions of the future of the world around us.